HETEROSIS AND COMBINING ABILITY STUDIES TO IDENTIFY THE SUPERIOR HYBRIDS AND PARENTS FOR GRAIN YIELD AND YIELD CONTRIBUTING TRAITS IN SORGHUM (Sorghum bicolor L. Moench) - K.N. YAMINI, D. SHIVANI; C.V. SAMEER KUMAR, SAIKIRAN VELDANDI, S. MAHESWARAMMA, K. SRAVANTHI, K. SUJATHA, S. RAMESH (The Journal of Research, PJTSAU, 2022)
A field experiment was conducted at Regional Agricultural Research Station (RARS), Palem to study the heterosis and combining ability of 64 genotypes for grain yield and yield related traits in sorghum [Sorghum bicolor (L.) Moench]. Fourteen parents including six male sterile (A lines) and eight restorers (R lines) were crossed in line × tester mating design to generate 48 F1 hybrids. Evaluation of hybrids along with the parents and standard checks (CSV-41 and CSH-16) was carried out using a Randomized Block Design during Rabi 2020-21. Data was collected on eight quantitative traits viz., days to 50 per cent flowering, days to maturity, plant height (cm), 100 seed weight (g), grain yield per plot (kg), grain yield per plant (g), fodder yield per plot (kg) and fodder yield per plant (g). Experimental results revealed that among the hybrids ICSA 418 × ICSR 13025 recorded maximum grain yield plant-1 with 81.77, 62.32, 60.12 and 50.46 percent heterosis over mid parent, better parent and standard checks (CSV- 41 and CSH-16), respectively. Variance due to sca was higher than gca and the ratio of variance of general to specific combing ability was less than unity for all the traits studied indicating the preponderance of non-additive gene action governing in the inheritance of these traits.